A service evaluation of implementation of RCPCH brain pathways clinical guideline linked to headsmart – be brain tumour aware (HeadSmart). (24th May 2012) - Wilne, S; Liu, JF; Clough, L; Dudley, J; Lakhanpaul, M; Kennedy, CR; Grundy, RG; Baker, M; Trusler, J; Carbury, P; Lindsell, S; Walker, DA
Abstract : Aims: To evaluate the impact of the HeadSmart Campaign upon symptom interval (SI) for newly diagnosed childhood brain tumours at UK Children's Cancer and Leukaemia Group (CCLG) treatment centres Introduction: HeadSmart national awareness campaign (www.headsmart.org.uk ) aims to disseminate the RCPCH endorsed Brain Pathways Guideline for referral of patients with symptoms suggestive of brain tumour. The campaign aims to reduce median SI for childhood brain tumours to 5 weeks in the UK. Methods: The SI experienced by children newly diagnosed with brain tumours in the UK was determined from Jan 2011 to Nov 2011 by HeadSmart Clinical Champions at 18 of 20 CCLG treatment centres reporting to an online database as part of a service evaluation under Caldicott guardian permission. Results: Data from 192 children (median age 6.3 year, range 0.11-16.9) is available. The median SI is 8.71 weeks (0 to 398 weeks). The median symptom onset to consultation with a healthcare professional interval is 2.4 weeks (0 to 123 weeks) and the median consultation to diagnosis interval is 3 weeks (0 to 398 weeks). Imaging that identified the tumour took place as an outpatient in 34.9%, an inpatient in 35.9% and from the emergency department in 19.8%. 2.1% of children were referred via a "two week wait" cancer referral. Tumour diagnoses were representative of population registries. The most frequent symptoms and signs at symptom onset were headache (41%), vomiting (41%), abnormal gait (13%), lethargy (12%) and abnormal coordination (12%); and at diagnosis were vomiting (51%), headache (49%), abnormal coordination (27%), lethargy (26%), abnormal gait (23%) and papilloedema (22%). The median symptom interval prior to launch of the HeadSmart campaign was 10.2 weeks and after the HeadSmart campaign 7.43 weeks (p=0.326). Conclusions: The median SI currently experienced by UK children with brain tumours has not changed over the last 23 years despite advances in the quality and availability of neuro-imaging. Analysis of the SI experienced by UK children before and after the HeadSmart launch suggests that the SI may have reduced. Further data collection is required to determine whether this reduction is sustained and statistically significant.